Моделирование двигателя внутреннего сгорания в задачах исследования гибридных транспортных средств - Бешта, Александр Степанович; Балахонцев, Александр Васильевич; Албу, Андрей Андреевич (НТУ "ХПИ", 2013)
The article describes mathematical model of the internal combustion engine. The model is built relative to instantaneous values of airflow and fuel rate and yields engine torque and speed. The model obtained is designed for integration into complex model of hybrid electric vehicle. Simulation results are shown.
Keywords: загрязнение окружающей среды; силовая энергетическая установка; гибридный автомобиль; электродвигатели; накопитель энергии; математическая модель ДВС